Impacts of Large-scale Land Investments on Income, Prices, and Employment: Empirical Analyses in Ethiopia. (August 2015) - Baumgartner, Philipp; von Braun, Joachim; Abebaw, Degnet; Müller, Marc
Highlights: We examine trend and types of large scale land acquisitions in Ethiopia since 1992. Using a farm model for one case in the far western low-land, impacts on resource use, income, and wages are assessed. We find a significant impact on natural resource use, poverty levels, and shadow prices of land and labor. Increasing inequality among local population is predicted. Summary: We review the trend and types of large-scale land transaction in Ethiopia since 1992 and assess the impacts of one such investment using four scenarios: (i) a baseline scenario; (ii) the forest loss resulting from the land transfer; (iii) the operation of the investment at full scale; and (iv) an alternative scenario of a smaller investment paired with a more inclusive rural development policy. Results showed that forest resources are important for the rural poor, but that losses can be offset by gains from employment generation and business opportunities. The alternative scenario indicated opportunities for better social and environmental sustainability.